2015
DOI: 10.1007/s13277-015-3628-3
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin 1-deficient cells upregulate SPOCK1: implications for prostate cancer progression

Abstract: Plakophilin (PKP) 1 is frequently downregulated in prostate cancer and therefore may play a tumor-suppressive role. In the present study, we stably knocked down PKP1 in the non-neoplastic, prostatic BPH-1 cell line. In the PKP1-deficient cells, the expression of keratin 14 was lost, and the apoptosis rate was significantly reduced indicating that the cells acquired new biological capabilities. Moreover, we analyzed the gene expression profile of the PKP1-deficient BPH-1 cells. Among the genes that were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Previous publications have demonstrated a role for SPOCK1 in cancer types such as breast cancer (Fan et al, 2016), prostate cancer Yang et al, 2015), glioblastomas , urothelial carcinomas (Ma et al, 2016), ovarian cancer , esophageal squamous cell carcinomas (Song et al, 2015), gallbladder cancer (Shu et al, 2015), lung cancer (Miao et al, 2013), and hepatocellular carcinomas (Li et al, 2013). All these studies focused on the epithelial fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have demonstrated a role for SPOCK1 in cancer types such as breast cancer (Fan et al, 2016), prostate cancer Yang et al, 2015), glioblastomas , urothelial carcinomas (Ma et al, 2016), ovarian cancer , esophageal squamous cell carcinomas (Song et al, 2015), gallbladder cancer (Shu et al, 2015), lung cancer (Miao et al, 2013), and hepatocellular carcinomas (Li et al, 2013). All these studies focused on the epithelial fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The SPARC family of proteins consists of SPARC (osteonectin), Hevin (SPARC-like protein 1), secreted modular calcium binding protein (SMOC) 1 and 2, testican-1, 2 and 3, and follistatin like protein 1 [ 18 ]. Members of the SPARC family share a follistatin-like domain and an extracellular calcium binding E-F hand motif, regulate extracellular matrix assembly and deposition, and modulate growth factor signaling pathways [ 18 , 19 ]. In the present study, we identified SPOCK1 as a novel MEC marker.…”
Section: Discussionmentioning
confidence: 99%
“…SPOCK1 expression was found to be significantly higher in prostate carcinoma compared with that in the normal prostate gland by both Oncomine data and the results of the present study. In previous studies, SPOCK1 was identified as a novel oncogene with critical effects on the PI3K/Akt and Wnt/β-catenin pathways, the Bcl-2 family and MMPs ( 12 , 13 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…EMT plays a key role in cancer metastasis, particularly in prostate neoplasms ( 25 ). Recent studies demonstrated that SPOCK1 regulates the EMT process during cancer metastasis ( 12 , 13 , 26 ). MMP3 and MMP9 are two mesenchymal markers that promote EMT and distant metastasis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation